Mathematics for mechanical engineers : problems and solutions - Omran, S. H.; Chaichan, M. T.; Hussen, H. M.; Nacy, N. G.; Habeeb, L. J. (Mercury Learning & Information, 2021)
This book provides over 250 quick review problems with complete, step-by-step solutions for all types of mechanical engineering exams. It covers all the important mathematical concepts used in mechanical engineering, physics, and other sciences, including functions, derivatives, integration, methods of integration, applications of integrals, matrices, complex numbers, and more. Excellent review of key mathematical topics prior to taking the exams.
Keywords: Mechanical engineering -- Mathematics.; elektronické knihy; electronic books